Pengaruh Variasi Media Pembelajaran Melalui Whatsapp Group Terhadap Motivasi Belajar PAI Siswa SD Negeri 6 Sumerta Tahun Pelajaran 2020/2021 - Putri, Nira Nuansari; Ismail, Syarof Nursyah; Arifin, Haris Nursyah (Faidatuna, 2021)
Generally, learning is done face-to-face in schools, but during the pandemic, the government implemented a physical distancing policy to suppress the spread of COVID-19, and learning was done online. SDN 6 Sumerta applies online learning with whatsapp groups, one of which is PAI learning. Learning motivation is one of the factors that influence the success of learning. Motivation is something that moves an individual to take an action. The purpose of this study was to determine: 1) The effect of variations in learning media in whatsapp group on PAI learning motivation of SDN 6 Sumerta students. 2) The contribution of the variation of learning media in the whatsapp group to the PAI learning motivation of SDN 6 Sumerta students. This type of research is quantitative with a correlational approach, the population is all Muslim students in grades I-VI SDN 6 Sumerta with a sample of 47 students, data collection techniques using questionnaires, documentation and observation. The results of the study show 1) there is a positive and significant influence on the variation of whatsapp group learning media on learning motivation. This is indicated by Y = 6.666 + 0.845X, meaning that if the variation of learning media in WhatsApp increases by 1 point, there will be an increase in learning motivation of 0.845. Judging from the f test, F_count is 610,424 > F_table in numerator 1 and denominator 31 at 4.16. Or it can be seen that significant > 0.05 is 0.000 < 0.05. This means that Ho is rejected and Ha is accepted. 2) Variables of learning media variation in whatsapp group contributed 90.3% to learning motivation. The remaining 9.7% is influenced by other factors not examined by the authors.